2009
DOI: 10.4012/dmj.28.454
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various visible light photoinitiators on the polymerization and color of light-activated resins

Abstract: The purpose of this study was to investigate effects of various visible light photoinitiators on the polymerization efficiency and color of the light-activated resins. Four photoinitiators, including camphorquinone, phenylpropanedione, monoacrylphosphine oxide (TPO), and bisacrylphosphine oxide (Ir819), were used. Each photoinitiator was dissolved in a Bis-GMA and TEGDMA monomer mixture. Materials were polymerized using dental quartz-tungsten halogen lamp (QTH), plasma-ark lamp and blue LED light-curing units,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
86
1
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 19 publications
2
86
1
6
Order By: Relevance
“…19 Alternative initiators are activated at different wavelengths that are not provided by the LEDs used, due to the short spectrum of light that they emit, which compromises the curing efficacy of this material. 20 Because manufacturers are usually reluctant to reveal the exact compositions of their products, 21 it is not possible to determine whether this situation explains the current results completely.…”
Section: Discussionmentioning
confidence: 97%
“…19 Alternative initiators are activated at different wavelengths that are not provided by the LEDs used, due to the short spectrum of light that they emit, which compromises the curing efficacy of this material. 20 Because manufacturers are usually reluctant to reveal the exact compositions of their products, 21 it is not possible to determine whether this situation explains the current results completely.…”
Section: Discussionmentioning
confidence: 97%
“…However, the spectral distribution of the output from the curing light source and the maximum absorption peak of a photoinitiator can affect the chemical and physical properties of a given resin. Some resinous photocure or dual cure materials, such as resin cements, may have a lower concentration of camphorquinone or other photoinitiator such as phenyl propanedione [28] (PPD) and monoacrylphosphine oxide [29] (TPO), and sometimes the percentage of photoinitiator is not clarified by the manufacturer because a patent on the product has been applied for. For Panavia F, the manufacturer omits the percentage of the camphorquinone-based photoinitiator system, and the percentage and composition of the photoinitiator component for RelyX ARC is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Although higher values of irradiance induce greater heat generation, the composite disk attenuated the temperature alteration caused by the LED since the composite had a low thermal conductivity [27,29], and did not affect the degree of conversion of the tested resin cements. The curing unit energy density did not influence the degree of conversion of Panavia F cured without ED primer, since QTH provided a significantly higher degree of conversion than the LED when ED Primer was not used.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the marked decrease in the light transmittance at shorter wavelengths observed was likely caused by higher scattering of light in the material. The wide and deep trough observed around 470 nm for all materials may have been due to light absorbance by the photoinitiator contained in the materials because the wavelength range was similar to the representative absorbance wavelength range of camphorquinone, a conventional photoinitiator often used in light-activated dental materials 15) . Our previous study reported that the filler particle in the composite resin played an important role for the light transmittance characteristics, including light diffusion characteristics, and color of the material 16) .…”
Section: Discussionmentioning
confidence: 99%